Ruin problem for a generalized Poisson process with reflection - Bratiichuk, N. S.; Lukovych, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider a generalized Poisson process with reflection at the level T > 0. Under certain conditions on the distribution of the values of positive jumps of the process, we obtain representations for the characteristic functions of functionals associated with the exit of the indicated process to the negative semiaxis.